JUSTIFICATION OF DIRECTIONS FOR IMPLEMENTING THE FINANCIAL POLICY OF THE ENTERPRISE - BASOK, Oleksandr; BILETSKA, Nataliia; IVANIUTA, Palvo; ZHUYKOV, Hennadii; DIACHUK, Ievgenii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article broadly reveals the essence of the financial policy of the enterprise, where its components are methods, mechanisms and tools for conducting analytical research and evaluation procedures. This is evidenced by the fact that due to the existence and observance of the financial policy at the enterprise, significant opportunities arise to identify more tangible reserves and potentials for the implementation of long-term goals and to ensure further development.This justifies the purpose of the article, which is a more in-depth study of the financial policy of the enterprise, which considers not only the activation of cash flows or the ability to perform payment transactions, but also the widespread conduct of analytical research and evaluation procedures. The most common process of implementation and implementation into actual achievements of the components of the financial policy is planning, due to which future directions of activity are predicted, which is evidenced by taking into account all the contributions available to the enterprise. Planning is mainly focused on clearly established goals, which include all existing results in accordance with the types and volumes of the contributed resources in translation into cost units. The same should be noted that planning has incorporated management mechanisms and tools for analytical research and evaluation procedures.Based on this, it is established that financial policy, having a complex that provides managers with ways and approaches to solving issues and problems, translating results and achievements into cost measurements, and even increasing competitiveness through the acquisition of advantages, through planning. This confirms that financial policy for each enterprise has a special purpose, due to which the continuity of its own activities occurs, for which all necessary means and resources are identified both in terms of sources and channels of acquisition and areas of use. This proves that the implementation features of financial policy are reflected in the sequence of its implementation in the internal space of the enterprise, which means identifying resource capabilities, reducing them to cost expressions, which reflects their combination with the results and achievements obtained.
Keywords: financial policy; planning; mechanisms; tools; indicators; financial condition